Blood pressure improvement after resection of non-functioning adrenal adenomas: influencing factors and serum metabolic features - Zhang, Jianlei; Wu, Peiqiang; Chen, Yule; Wang, Min; Song, Wenbin (Frontiers in Molecular Biosciences, 2025)
IntroductionNon-functioning adrenal adenomas (NFAs) are typically regarded as benign tumors that lack hormonal secretion. However, emerging evidence has shown that some patients with NFAs and hypertension experience improvements in blood pressure after adrenalectomy, indicating a potential correlation between NFAs and hypertension. Nevertheless, the precise mechanisms that underpin this phenomenon remain elusive.MethodsWe collected data from all patients with adrenal adenomas who underwent unilateral laparoscopic partial or total adrenalectomy at the First Affiliated Hospital of Xi’an Jiaotong University in 2023. A statistical analysis was conducted on factors such as tumor diameter, duration of hypertension, BMI, and age. Additionally, we gathered serum samples from six patients who experienced postoperative blood pressure improvement and six patients who did not. These samples were subjected to targeted and untargeted metabolomic analyses to identify significant serum metabolites.ResultsOur findings revealed that 50.9% of patients with NFAs and hypertension experienced blood pressure improvement after surgery. Additionally, patients in the improvement group (IG) exhibited larger tumor diameters alongside shorter durations of hypertension compared to their counterparts in the nonimprovement group (NIG). Untargeted metabolomic analysis identified 89 differentially abundant metabolites in the serum between the IG and NIG. In particular, we found that guanidinoacetic acid (GAA), a precursor of creatine synthesis that possibly participates in the occurrence of hypertension, was enriched in patients in the IG and reduced after surgery.DiscussionThe findings of our study indicated that duration of hypertension and tumor diameter may exert an influence on the extent of postoperative blood pressure improvement, and NFAs might promote hypertension through GAA-related creatine metabolism.